Development of e-worksheet based on search, solve, create, and share (SSCS) Islamic context to improve science process skills on excretory system material - Tika Audyta Elvanuari; Z. Zulfiani; Eny Supriyati Rosyidatun (University of Muhammadiyah Malang, 2024)
Electronic student worksheets (e-worksheet) are needed as alternative teaching materials in learning. This study aims to produce teaching materials in the form of e-worksheet based on Search Solve Create and Share (SSCS) Islamic context to improve science process skills on class XI excretory system material that is worthy of the results of validity, responses of students and biology teachers. This research was conducted at MAN 1 Bogor. The research model used is a 4D model (Define, Design, Develop, Disseminate), but in research only to the development stage (Develop). The e-worksheet teaching materials developed are tested for validity. The results of validity tests by design and media experts obtained 89% in the very decent category, material expert assessments obtained 84% in the very feasible categories, and expert assessments of Islamic religious education obtained 100% in the very feasible categories. The results of student responses obtained percentages of 89% in limited trials and 89.7% in expanded trials. Based on the findings of the research results, it can be concluded that E e-worksheet based on Search Solve, Create and Share (SSCS), an Islamic context to improve science process skills on the excretory system material developed, is very feasible to be used and applied to biology learning.